2018
DOI: 10.22219/jpbi.v4i1.5489
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for establishing networking with partner schools for implementing lesson study in Indonesia

Abstract: Lesson Study for Learning Community (LSLC) contains two terminologies underpinning one another. There are many difficult challenges when the plan to create LSLC surfaces. Therefore, strong motivation and precise implementation strategies are of urgency. One of the ways is by developing networking of LSLC between universities and partner schools. The LSLC program will become powerful when it is done collaboratively in a form of strong partnership connected by networks. Writing this article aims to describe stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
1
15
0
2
Order By: Relevance
“…The above assumptions are in line with some previous studies which reported that the low communication skill can be caused by the both external and internal factors: 1) the low learning motivation of students (Filak & Sheldon, 2008;Kitsantas & Zimmerman, 1998;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Wicaksono, Minarti, & Roshayanti, 2018), 2) the students' passive habit in learning, 3) the low ability in mastering language components, 4) the low quality of students' mentality, 5) the bad interactions between teacher and students (Hodge & Anderson, 2007), 6) the low interaction quality among students, and 7) the improper learning media utilized by teacher (Firdausi, Prabawa, & Sutarno, 2017;Putra, Abdurrahman, & Suana, 2015;Spiliotopoulos, Antonakaki, Ioannidis, & Fragopoulou, 2016) Students' communication skill can be optimized through various ways. Cholvistaria, (2012); Siska et al (2013);and Tuada et al (2017) stated that to enact this skill, students could be motivated to implement science process in their daily communication particularly during discussion and presentation sessions.…”
Section: Students' Scientific Process Skills In West Ilirsupporting
confidence: 90%
“…The above assumptions are in line with some previous studies which reported that the low communication skill can be caused by the both external and internal factors: 1) the low learning motivation of students (Filak & Sheldon, 2008;Kitsantas & Zimmerman, 1998;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Wicaksono, Minarti, & Roshayanti, 2018), 2) the students' passive habit in learning, 3) the low ability in mastering language components, 4) the low quality of students' mentality, 5) the bad interactions between teacher and students (Hodge & Anderson, 2007), 6) the low interaction quality among students, and 7) the improper learning media utilized by teacher (Firdausi, Prabawa, & Sutarno, 2017;Putra, Abdurrahman, & Suana, 2015;Spiliotopoulos, Antonakaki, Ioannidis, & Fragopoulou, 2016) Students' communication skill can be optimized through various ways. Cholvistaria, (2012); Siska et al (2013);and Tuada et al (2017) stated that to enact this skill, students could be motivated to implement science process in their daily communication particularly during discussion and presentation sessions.…”
Section: Students' Scientific Process Skills In West Ilirsupporting
confidence: 90%
“…Kebermanfaatan kolaborasi dapat dirasakan, baik pada proses pembelajaran hingga proses pengajaran. Salah satu implementasi kegiatan kolaboratif yang telah terbukti mampu meningkatkan kualitas pengajaran adalah LS (Cajkler, Wood, Norton, & Pedder, 2013;Chenault, 2017;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018 Sub-permasalahan yang diterima oleh masing-masing kelompok direspon oleh kelompok tersebut melalui penyusunan pertanyaan "Apa", "Bagaimana", "Dimana", "Kapan", "Siapa", dan "Mengapa" (ABDIKASIM) beserta jawabannya 3…”
Section: Hasil Dan Pembahasanunclassified
“…Lesson study (LS) has become a model for developing teacher professionalism in various countries., including Indonesia (Lieberman, 2009;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Saito et al, 2018;Yalcin Arslan, 2019). The development of LSLC in the world is increasing, not only shown from the number of practitioners in schools, but also shown from the results of research, the emergence of various Lesson study communities such as Professional Learning Community (PLC) in various countries, as well as scientific forums such as the Word Association of Lesson Studyes (WALS).…”
Section:  Introductionmentioning
confidence: 99%
“…PIGP was developed and implemented using the Lesson Study approach to accelerate the professionalism of novice teachers (Copriady, 2013). Pilot schools are also carried out as an effort to initiate educational institutions to learn to develop Lesson Study as a means of improving the quality of learning (Nurwidodo et al, 2018;Hindun, Nurwidodo, Wahyono, Miharja, & Rais, 2018). These efforts have been carried out intensively, but often are not in line with learning expectations.…”
Section:  Introductionmentioning
confidence: 99%